Palestine, Paledtinias and international law - Boyle, Francis A (Atlanta, USA Clarity Press, INC, 2003)
Palestine, Palestinians and International Law provides a comprehensive survey of the international legal principles related to the Palestinian struggle for self-determination - from the League of Nations Mandate for Palestine awarded to Britain after WWI, through the partition of the Palestine Mandate by the United Nations after WWII, the Palestinian Declaration of an Independent State in 1988, the diplomatic recognition of the Palestinian state by nearly 130 other states, to the United Nations granting the State of Palestine all rights of a UN member state but the right to vote
Keywords: Arab-Israeli conflict; International law; Palestinians; Palestine